To build a fire and other stories - London, Jack 12/01/1876-22/11/1916 (New York : Popular Library, 1967)
This edition is for readers for whom English is a second language. It can be anyone whos has learned 2,000 words of english.
Glossary.
Keywords: Cuentos; Estados Unidos De America; Literatura Norteamericana